Microwave-assisted synthesis and development of novel penicillinoate@copper metal-organic frameworks as a potent antibacterial agent - Abdulkadhim, Adnan Hashim; Husein Kamona, Suhair Mohammad; Shamikh Al-Saedi, Haider Falih; Taki, Anmar Ghanim; Hamoody, Abdul-Hameed. M.; Hamood, Sarah A.; Rab, Safia Obaidur; Amir, Ahmed Ali; Kareem, Ashwaq Talib; Alawadi, Ahmed; Ihsan, Ali (Frontiers in Chemistry, 2024)
Recently, nanoscience, especially metal–organic frameworks (MOFs), has been used to increase the effectiveness and properties of drugs. In this study, by using microwave irradiation; penicillin, which is a known antibiotic; and copper metal–organic frameworks (Cu-MOFs), a new penicillinoate@copper metal–organic framework (penicillinoate@Cu-MOF) was synthesized. The structure and characterization of the newly synthesized compound were determined using FT-IR spectrums, EDAX analysis, elemental analysis, XRD patterns, SEM images, nitrogen adsorption/desorption curves, and TGA curve. Then, its antimicrobial effects were evaluated on numerous Gram-positive and Gram-negative bacterial strains and were compared with those of penicillin and gentamicin. In continuation of the biological activities, antioxidant tests were performed on the compounds using the DPPH method. For biological activities, the synthesized penicillinoate@Cu-MOF is much more effective than penicillin and Cu-MOF. The loading of penicillin on the nanostructure and the presence of copper in the final composition can be attributed to the high antibiotic properties of the synthesized composition.